Sub-cellular sequestration of alkaline drugs in lysosomes: new insights for pharmaceutical development of lysosomal fluid - Malaz Yousef; Tyson S Le; Jieyu Zuo; Chulhun Park; Nadia Bou Chacra; Neal M Davies; Raimar Löbenberg (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Lysosomal-targeted drug delivery can open a new strategy for drug therapy. However, there is currently no universally accepted simulated or artificial lysosomal fluid utilized in the pharmaceutical industry or recognized by the United States Pharmacopeia (USP). Experimental procedure: We prepared a simulated lysosomal fluid (SLYF) and compared its composition to a commercial artificial counterpart. The developed fluid was used to test the dissolution of a commercial product (Robitussin®) of a lysosomotropic drug (dextromethorphan) and to investigate in-vitro lysosomal trapping of two model drugs (dextromethorphan and (+/-) chloroquine). Findings/Results: The laboratory-prepared fluid or SLYF contained the essential components for the lysosomal function in concentrations reflective of the physiological values, unlike the commercial product. Robitussin® passed the acceptance criteria for the dissolution of dextromethorphan in 0.1 N HCl medium (97.7% in less than 45 min) but not in the SLYF or the phosphate buffer media (72.6% and 32.2% within 45 min, respectively). Racemic chloroquine showed higher lysosomal trapping (51.9%) in the in-vitro model than dextromethorphan (28.3%) in a behavior supporting in-vivo findings and based on the molecular descriptors and the lysosomal sequestration potential of both. Conclusion and implication: A standardized lysosomal fluid was reported and developed for in-vitro investigations of lysosomotropic drugs and formulations.